Techno-economic and Performance Assessment of a Hybrid Fuel Cell-based Combined Heat and Power System for a Dairy Industry - Kashif Najeeb (328910); Dr. Muhammad Hassan (USPCAS-E, NUST,Islamabad, 2023)
TH-496
Keywords: MS Thesis; MS-EEP Thesis